An egalitarian disease? Socioeconomic status and individual survival of the Spanish Influenza pandemic of 1918 - 19 in the Norwegian capital of Kristiania - Svenn-Erik Mamelund (University of Oslo, Department of Economics, 2004)
The Spanish Influenza pandemic of 1918-19 was one of the most devastating diseases in history, killing perhaps as many as 50-100 million people worldwide. In addition to the high death toll and the high general lethality, the disease had a peculiar feature: the largest increase in death rates occurred among those between the age of 20 and 40 as opposed to the very young and the elderly, which is the more typical pattern of influenza epidemics. Furthermore, it appeared that it was the most robust population groups and the previously healthy that had highest mortality rates. Much of the literature favors the view that Spanish Influenza was class neutral with respect to mortality. This paper uses individual level data and applies Cox regressions to test the hypothesis that the blue-collar working class in 1918 suffered higher death rates from Spanish Influenza than the bourgeois and white-collar middle class in two parishes of the Norwegian capital of Kristiania (renamed Oslo in 1924).
Keywords: I12; J10; 330; Spanish Influenza mortality 1918-19; individual survival; Norway; event history analysis; Cox proportional hazards; Sterblichkeit; Infektionskrankheit; Sozialer Status; Norwegen